The Influence of Health Education via WhatsApp Media on the Level of Knowledge of Adolescents about Gastritis - Siti Vannisa Rachmatika; Nilowfar Salighehdar (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study aims to determine the effect of health promotion through social media whatsapp on adolescent knowledge about gastritis in State High School 03 Bengkulu City. Methodology: The type of research used was the Pre Experimental One Group Pre test and Post test design. The sample in this study was students of class X State High School 03 Bengkulu City, amounting to 30 people, sampling using purposive sampling techniques were analyzed usingtest Wilcoxon. Main Findings: The results obtained by the average knowledge before (7.1000) and after (13.9667). The results of increased knowledge before to after that is (15.50) test results Wilcoxon obtained p value = 0.000 < 0.05 which shows there is an influence after being given health promotion through social media whatsapp about gastritis in adolescents at State High School 03 Bengkulu City. Novelty/Originality of this study: This study found that health promotion through WhatsApp social media significantly increased adolescents' understanding of gastritis, indicating that this instant messaging platform can be an effective and easily accessible health education tool to increase awareness and encourage behavioral change in the adolescent age group.